2021
DOI: 10.1016/j.omtm.2021.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and organ-specific metastasis

Abstract: The transmission of information between tumor cells and other cell types in the tumor microenvironment plays an important role in tumor metastasis and is critically modulated by exosomes and other mediators. Tumor-derived exosomes can promote epithelial-mesenchymal transition, angiogenesis, immune escape, formation of the pre-metastatic microenvironment, and transmission of drug-resistant molecules, thereby promoting tumor growth, invasion, and metastasis. Integrins are important regulatory molecules on exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 153 publications
(213 reference statements)
0
18
0
Order By: Relevance
“…Since the final objective of the study was to enable the visualization of the ability of EVs MSCs to target tumors, the imaging properties such as T 1 and T 2 relaxation times of derived PERFECTA-EVs MSCs were first evaluated in phantoms to assess their suitability for further use in vivo. In fact, there is strong evidence that EVs (i.e., B16-F10) from cancer cells are heavily involved in metastatic tumor growth, which would make their therapeutic use questionable.…”
Section: Resultsmentioning
confidence: 99%
“…Since the final objective of the study was to enable the visualization of the ability of EVs MSCs to target tumors, the imaging properties such as T 1 and T 2 relaxation times of derived PERFECTA-EVs MSCs were first evaluated in phantoms to assess their suitability for further use in vivo. In fact, there is strong evidence that EVs (i.e., B16-F10) from cancer cells are heavily involved in metastatic tumor growth, which would make their therapeutic use questionable.…”
Section: Resultsmentioning
confidence: 99%
“…A study has found that human melanomaderived exosomes are rich in exosomal miR-155 and miR-210. These exosomal miRNAs reprogram human adult dermal fibroblasts by promoting glycolysis and inhibiting oxidative phosphorylation (OXPHOS), leading to the acidification of ECM [257,281]. The local acidification of ECM is conducive to the formation of tumor pre-metastasis niches.…”
Section: Exosomal Cargos Remodel Ecm Through Metabolic Reprogrammingmentioning
confidence: 99%
“…Integrin glycoprotein has 2 subunits such as alpha (18 types) and beta (8 types). All alpha and beta subunits combinedly 24 cell signaling legends express which leads to organ-specific metastasis (Zhao et al, 2021). In lung cancer bone metastasis (α4β1, αVβ6, αVβ3), liver metastasis (α5β1, α2β1, αVβ5), brain metastasis (αVβ3, αVβ5, αVβ8), and lymph node metastasis (α4β1, αVβ7) are regulated via integrin (Zhao et al, 2021).…”
Section: Role Of Evs In Ards/alimentioning
confidence: 99%